Solutions to poorly defined subjects - Edwards, Chris (The Estates Gazette, 2009)
The paper examines the law on tenants' alterations and reviews how the service charge might be apportioned where the lease prescribes that a floor area apportionment be used and shows possible outcomes dependent upon the wording used. Consideration is also given to leases that are less prescriptive as to the method of apportionment, referring only to a "fair and reasonable proportion as determined by the Landlord's Surveyor".